2008
DOI: 10.1152/ajprenal.90300.2008
|View full text |Cite
|
Sign up to set email alerts
|

Salt-sensitive hypertension and cardiac hypertrophy in mice deficient in the ubiquitin ligase Nedd4-2

Abstract: . Salt-sensitive hypertension and cardiac hypertrophy in mice deficient in the ubiquitin ligase Nedd4-2. Am J Physiol Renal Physiol 295: F462-F470, 2008. First published June 4, 2008 doi:10.1152 doi:10. /ajprenal.90300.2008 has been proposed to play a critical role in regulating epithelial Na ϩ channel (ENaC) activity. Biochemical and overexpression experiments suggest that Nedd4-2 binds to the PY motifs of ENaC subunits via its WW domains, ubiquitinates them, and decreases their expression on the apical memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 37 publications
3
134
3
3
Order By: Relevance
“…Because their genetic background was similar to ours (although not identical), it is possible that those mice contain a shorter splice isoform of Nedd4L [suggested from a Nedd4L immunoblot (28)] that may help explain the milder phenotype. Another possibility is that because these mice lacked Nedd4L throughout embryonic development, other Nedd4 family E3 ligase(s) might have compensated for the loss of Nedd4L in the lung.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Because their genetic background was similar to ours (although not identical), it is possible that those mice contain a shorter splice isoform of Nedd4L [suggested from a Nedd4L immunoblot (28)] that may help explain the milder phenotype. Another possibility is that because these mice lacked Nedd4L throughout embryonic development, other Nedd4 family E3 ligase(s) might have compensated for the loss of Nedd4L in the lung.…”
Section: Discussionmentioning
confidence: 81%
“…Knockout of Nedd4L in Lung Epithelia Leads to Increased ENaC Expression and Function. Because Nedd4L is known to inhibit ENaC when expressed in tissue culture cells or in Xenopus oocytes (11,14,15,28), we tested using several approaches, whether loss of Nedd4L in type II and Clara cells leads to increased ENaC expression and function in vivo in the lung. First, we assessed levels of ENaC protein expression in lungs using immunostaining of lung sections and isolated type II cells under nonpermeablilizing condition (biochemical analysis using immunoblotting was not feasible due to insufficient number of type II cells that can be isolated from the mice).…”
Section: Mice Lacking Nedd4l In Lung Epithelia (Spc-expressing Cells)mentioning
confidence: 99%
“…Indeed, these mice displayed impaired Na + excretion and hypertension, apparently mediated by ENaC overactivity (25). No effect on NCC was observed.…”
Section: Introductionmentioning
confidence: 90%
“…Generation of constitutive Nedd4L KO mice, by removing exons 6 to 8 of the Nedd4L gene (Nedd4L-Δ6-8 KO mice), demonstrated the importance of NEDD4-2 in the control of ENaC activity and blood pressure (25). Indeed, these mice displayed impaired Na + excretion and hypertension, apparently mediated by ENaC overactivity (25).…”
Section: Introductionmentioning
confidence: 99%
“…A recent transgenic mouse model harboring a Nedd4-2 gene deletion was shown to develop a severe form of salt-sensitive hypertension, suggesting that Nedd4-2 is a limiting factor in the aldosterone-dependent signaling cascade. 52 Fava et al 53 reported that 24-hour ambulatory blood pressure monitoring was linked to chromosome 18q21-22, and genetic variation of Nedd4-2 associates with crosssectional and longitudinal blood pressure in Swedes. In a linkage study of 16 markers (including 2 SNP markers located within the Nedd4-2 gene) on chromosome 18 between 70 and 104 cM and ambulatory blood pressure, in 118 families, the strongest evidence of linkage was found for 24-hour and daytime systolic ambulatory blood pressure monitoring at the Nedd4-2 locus (82.25 cM).…”
Section: ␥Enacmentioning
confidence: 99%